Cooperative Learning with Jigsaw Type for Teaching Nahwu - Erna Puspita; Hanik Mahliatussikah; Ibnu Samsul Huda (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The teaching of Nahwu in Islamic boarding schools is often hindered by monotonous, teacher-centered methods that limit students’ comprehension and engagement. Specific Background: At Daarul Abror Modern Islamic Boarding School, Grade II-C students displayed low achievement in Nahwu due to limited interactive and contextualized learning. Knowledge Gap: While the Jigsaw cooperative learning model has been shown to improve language skills in other contexts, its application in teaching Nahwu with the Nahwu Wāḍiḥ text in modern pesantren remains underexplored. Aims: This study investigates the effectiveness of the Jigsaw method in enhancing students’ comprehension of Nahwu and fostering active participation. Results: Using a qualitative case study with observations, interviews, and pre–post tests, findings reveal improved mastery of grammatical structures, higher test scores (from 62.60% to 68.90%), and increased student motivation and collaboration. Novelty: Unlike prior studies limited to Arabic or English descriptive texts, this research applies the Jigsaw strategy specifically to Nahwu instruction within a modern pesantren framework. Implications: The study highlights the potential of cooperative learning to strengthen both cognitive and social aspects of students’ learning, offering teachers a practical model to promote deeper comprehension, accountability, and engagement in grammar instruction. Highlights: Jigsaw method improved students’ comprehension and motivation in Nahwu. Pre–post tests showed higher achievement after implementation. Cooperative learning fosters collaboration and accountability. Keywords: Jigsaw Technique, Nahwu Learning, Cooperative Learning, Pesantren Education, Student Engagement